Patient decision aid for trial of labor after cesarean (TOLAC) versus planned repeat cesarean delivery: a quasi-experimental pre-post study - Kartik K. Venkatesh; Suzanne Brodney; Michael J. Barry; Jamie Jackson; Kiira M. Lyons; Asha N. Talati; Thomas S. Ivester; Maria C. Munoz; John M. Thorp; Wanda K. Nicholson (BMC, 2021)
Abstract Objective To assess the impact of a web-based decision aid on patient-centered decision making outcomes among women considering a trial of labor after cesarean (TOLAC) versus planned repeat cesarean delivery. Methods The Birth Decision Aid Study (B-READY) was a quasi-experimental pre-post study of two sequential cohorts. From June 18, 2018 to July 31, 2019, 50 women were enrolled in routine care, followed by 50 women who were enrolled in the decision aid group. Inclusion criteria were singleton pregnancies between 19/0 to 36/6 weeks, ≤2 prior cesareans, and no contraindications to TOLAC. The decision aid group viewed the online Healthwise® "Pregnancy: Birth Options After Cesarean" program. Both groups received the same birth options counseling and completed the same online assessment. Primary patient-centered outcomes were knowledge about birth options and shared decision making at online assessment, and informed, patient-centered decision making about her preferred mode of delivery at delivery admission. Results Among 100 women participated in this study (50 per group), the mean gestational age at enrollment was 31 weeks, and 71% or 63/89 women who consented to delivery data abstraction had a cesarean delivery. Women in the patient decision aid group gained more knowledge (defined as score ≥ 75%) about birth options compared to those in the routine care group (72% vs. 32%; adjusted odds ratio, AOR: 6.15 [95% CI: 2.34 to 16.14]), and were more likely to make an informed, patient-centered decision (60% vs. 26%; AOR: 3.30 [95% CI: 1.20 to 9.04]. Women in both groups reported similar involvement in shared decision making, as well as satisfaction and values. More than 90% of decision aid users reported it was a useful tool and would recommend it to other TOLAC-eligible women. Conclusions A web-based birth options patient-centered decision aid for TOLAC eligible women can be integrated into prenatal Telehealth and may improve the quality of decision making about mode of delivery. Trial registration The study was registered with ClinincalTrials.gov and the ID# was NCT04053413 . Registered 12 August 2019 - Retrospectively registered.